Determinants of professional careers of bachelor's degree graduates : the faculty of tourism and recreation - Podoska-Filipowicz, Elzbieta (Array, 2008)
Tourism has recently been one of the fast developing industries in Poland and all over the world.;;It is an important source of job opportunities. The estimated global rate of employment in tourism;;management is 10% of the total employment rate. It also makes a significant contribution to the gross;;domestic product. Globally, it is estimated as 10%.;;Tourism has recently been one of the fast developing industries in Poland and all over the world. It is an;;important source of job opportunities. The characteristics of the contemporary labour market with regard to;;tourism include:;;• seasonal character of employment,;;• part-time employment,;;• high percentage of women employees,;;• demand for employees of different fields and occupations, who may be employed in tourism;;management directly (hospitality, catering, direct tourist traffic service) or indirectly (trade, transport,;;banking, administration, manufacturing of: sports and tourist equipment, foodstuffs and other) –;;complementary employment in the sphere of tourist traffic service,;;• options of professional activity for the retired and the pensioners (seasonal character of employment),;;• seasonal and part-time job opportunities for pupils and students